Synergizing Stakeholders in Reducing Risk of Earthquake and Tsunami-Disaster in the Most Vulnerable Area - Putera, Roni Ekha; Nurasa, Heru; Sugandi, Yogi Suprayogi (UI Scholars Hub, 2018)
Natural disaster is a multidimensional problem in nature caused by multiple factors yet predominantly coming to happen by the acts of humans. Realizing this leads to an indispensable need for synergy between multiple stakeholders. While Indonesia is taken as a case for it is so vulnerable of disaster occurrence, Padang City becomes the most vulnerable area in the world. This article seeks to explain efforts undertaken by the local government and the support from the community, nongovernmental organizations (NGOs), and business sector. The research method used in this article in interpretive qualitative method by data collection through observation, interview, and document review. The informants in this study consist of related offices of the municipal government of Padang, community representative, NGOs, and corporations. As for the result of this research, it shows that there is a synergy between the local government and disaster stakeholders that is evident in earthquake- and tsunami risk reduction activities conducted by the municipal government involving the community, NGOs and business world. The activities include the making of fixed procedure of disaster management, disaster evacuation simulation, disaster training at community and school level, and changes of the recent Padang Municipal Spatial Planning.